Determinants of Online Customers' Attitudinal Loyalty and Impulsive Purchasing on Shopee: The Role of Visual Engagement and Enjoyment - Indriyarti, Eko Retno (Universitas Bunda Mulia, 2025)
Despite its popularity and substantial user support, e-commerce in Indonesia exhibits intense rivalry for survival. This is demonstrated by the decrease in e-commerce in Indonesia, attributable to insolvency, changes in business models, or a decision to refrain from operating in the country. Amidst intense competition, Shopee has managed to endure and enhance its brand and services, establishing itself as one of the largest and most formidable e-commerce enterprises in Indonesia. Several factors encourage Indonesian customers to engage in impulsive and loyal shopping on a platform. This study seeks to examine the factors influencing impulsive buying on Shopee, utilizing predictor variables such as visual engagement, enjoyment, and attitudinal loyalty. This quantitative study employs a questionnaire as a survey instrument for participants. The items in the questionnaire are derived from prior research. A 5-point Likert scale is employed to assess the value of respondents' answers. This study utilized a sample of 200 respondents selected by purposive procedures, specifically persons who had made purchases on Shopee. This research employs partial least squares structural equation modeling (PLS-SEM) and SmartPLS as analytical instruments. This study's findings indicate that customer satisfaction on the Shopee platform can affect both attitudinal loyalty and impulsive purchasing behavior. Conversely, the visual engagement experienced by Shopee customers can solely affect impulsive purchasing, rather than fostering attitudinal loyalty. Moreover, attitudinal loyalty exerts no influence on impulsive purchasing. Additional findings indicate that attitudinal loyalty does not function as a mediator in this research. This study's findings enhance strategies for cultivating client loyalty and stimulating impulsive purchases by evaluating the reinforcement of visual engagement or enjoyment factors. This study's limitations and recommendations for future research are to the range of predictor variables and the necessity for a larger, more diverse sample size.